Naturally better? A review of the natural‐is‐better bias. Issue 8 (30th July 2019) - Meier, Brian P.; Dillard, Amanda J.; Lappas, Courtney M.
Abstract: People are frequently exposed to products and services that are labeled natural (e.g., Nature Made Vitamins or GoJo Natural Orange Hand Cleaner). The frequency with which this label is used suggests that it delivers an advantage in marketing and sales. Our review examines the preference for and perception of naturalness and reveals that people have a bias for items described as natural in many domains including foods, medicine, beauty products, cigarettes, and lighting. These preferences abound even when the natural item is identical or not objectively better than the non‐natural or synthetic item. We believe this bias may be driven by a natural‐is‐better default belief as well as the belief that natural items are safer than non‐natural items. Although a bias for natural items is apparent, this literature is in its infancy, and we suggest three areas that will help build and refine the empirical research base and theory: the measurement of behavior, the examination of individual differences, and the development of methods for reducing the bias. A better understanding of the naturalness bias relevant to these areas will lead to a more comprehensive understanding of the area, including factors that may cause and reduce it.